Human rites : the power of rituals, habits, and sacraments - Johnson, Dru (Grand Rapids, MI. William B Eerdmans Publishing Company, 2019)
What are we doing when we gather around the sacraments -- or when we make the same breakfast every morning? Embodying rituals, says Dru Johnson. And until we understand what we're doing and why, we won't know how these rituals work, what they mean, or how we might adapt them. In Human Rites Johnson considers the concept of ritual as seen in Scripture and its role in shaping our thinking. He colorfully illustrates both the mundane and the sacred rituals that penetrate all of life, offering not only a helpful introduction to rituals but also a framework for understanding them. As he unpacks how rituals pervade every area of our lives, Johnson suggests biblical ways to focus our use of rituals, habits, and sacraments so that we can see the world more truly through them
Introduction : Know your rites -- Our Ritualed World . More than mind games -- Guided by voices -- Our Ritual Guides. Priestly monkeys banging on their ritual typewriters -- All journeys have a secret destination -- When Rites Go Wrong. When rites go dark -- When rites go flimsy -- Rituals in Christian Religion. Getting some distance from our sacraments -- Avoiding the ethical rift -- Riting our wrongs -- Practicing safe ritual improvisation -- Coda -- Appendix : Examples of a ritual inventory
Includes bibliographical references
Keywords: Ritualism; Ritual; Rites and ceremonies; Sacraments